Panchayat Elementary Education Officer Educational Administrative Decentralisation in Rajasthan - Payal, Ruchi (JOURNAL OF INDIAN EDUCATION, 2023)
In the context of developments in the administration and management of the Education Department in Rajasthan, the addition of Panchayat Elementary Education Officers (PEEO) can be a game changer. This article explores the roles, duties, challenges, and enormous potential of the PEEOs, who are a product of the educational decentralisation drive. It was introduced to increase the efficiency of schools in rural areas, but these new administrators are facing many challenges that are not studied until now. The former part of the study includes the policy provisions regarding PEEO’s, methodology with the semi-structured interview as tool of relevant officers in three Panchayats of Jhunjhunu district of Rajasthan, objectives of the study and questions. The latter part includes grassroot observations, ground realities, challenges and suggestions for further reforms by the policy planners. The lessons learned in this context will have broad implications for the theory and practice of decentralisation in education. .